Anticonvulsant activity of Nigella sativa, Aegle marmelos and Benincasa hispida in Pentylenetetrazole induced seizure in Swiss albino mice - Edavan Puthallath, Rejeesh; Joseph, Lovelyn; Kademane, Kumaraswamy; Narayan Rao, Sudarshanram (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: To test anticonvulsant properties of three medicinal plants with pentylenetetrazole induced seizure test in Swiss albino mice. Materials and Methods: Herbs selected for the work (leaves of Aegle marmelos, seed of Nigella sativa, and fruit of Benincasa hispida) were collected locally from Mangalore, India and were authenticated by a Taxonomist. Aqueous extract of Aegle marmelos leaves (AmAE) and Ethanolic extract of Nigella sativa seeds (NsEE) were prepared by Soxhlet extraction and separated from solvent using a water bath. Benincasa hispidafruit juice (BhE) was filtered and dried on a water bath. Qualitative phytochemical analysis of the test extracts were done with Preliminary chemical reaction tests, and Liquid chromatography–mass spectrometry (LC/MS). Male Swiss albino mice, 3-4 months of age, weighing 25-30g were used in the study. Extracts and vehicle were administered orally 1 hour prior to inducing convulsions. Test employed for screening anticonvulsant properties was Pentylenetetrazole (PTZ) induced seizure test [60mg/kg/i.p]. Animals were treated with extracts at a dose of 900mg/kg orally. The results were compared with control group and test for analysis of variance and significance were done (ANOVA, Dunnett’s test). Results: Aqueousextract of Aeglemarmelos leaves and Ethanolic extract of Nigella sativa seeds possess anticonvulsant property in Pentylenetetrazole (PTZ) induced seizure model, Crude extract of Benincasahispida fruits did not show statistically signifi cant anticonvulsant property. Conclusions: Aeglemarmelos leaf and Nigella sativa seed possess anticonvulsant properties in pentylenetetrazole induced seizures, this is in accordance with many other published reports on the same herbs with different animal models and indicates effectiveness in human absence seizure patients. Asian Journal of Medical Sciences Vol. 7(3) 2016 97-102